1997
DOI: 10.1177/002246699703100102
|View full text |Cite
|
Sign up to set email alerts
|

Research on Inclusive Educational Programs, Practices, and Outcomes for Students with Severe Disabilities

Abstract: Nineteen research investigations of inclusive educational programs, practices, and outcomes for students with severe disabilities are reviewed. The studies represent a broad diversity of questions, methodologies, and participants. The focus of each investigation fell into one of five categories: (a) parents' perceptions of the pursuit and impact of inclusive educational placement, (b) issues and practices in inclusive schools and classrooms, (c) the cost of inclusive educational placement, (d) educational achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 32 publications
2
106
0
7
Order By: Relevance
“…All keywords were truncated to take into account grammatical differences (i.e., mental retard# to include mental retardation and mentally retarded). In addition, a careful examination was conducted of the references from the identified studies themselves and from review articles (Baker et al, 1994(Baker et al, -1995Carlberg & Kavale, 1980;Gottlieb, 1981;Gresham, 1982;Guralnick, 1999;Hallenbeck & Kauffman, 1995;Hunt & Goetz, 1997;Klassen, 1994;Leinhardt & Pallay, 1982;Lipsky & Gartner, 1995;Madden & Slavin, 1983;Sindelar & Deno, 1978 Butera, & Lesar, 1991). In addition, studies were excluded in which nondisabled students were asked about their perceptions of &dquo;children with disabilities&dquo; in general (i.e., Helmstetter, Peck, & Giangreco, 1994;Schnorr, 1990).…”
Section: Methods Criteria For Including a Studymentioning
confidence: 99%
See 1 more Smart Citation
“…All keywords were truncated to take into account grammatical differences (i.e., mental retard# to include mental retardation and mentally retarded). In addition, a careful examination was conducted of the references from the identified studies themselves and from review articles (Baker et al, 1994(Baker et al, -1995Carlberg & Kavale, 1980;Gottlieb, 1981;Gresham, 1982;Guralnick, 1999;Hallenbeck & Kauffman, 1995;Hunt & Goetz, 1997;Klassen, 1994;Leinhardt & Pallay, 1982;Lipsky & Gartner, 1995;Madden & Slavin, 1983;Sindelar & Deno, 1978 Butera, & Lesar, 1991). In addition, studies were excluded in which nondisabled students were asked about their perceptions of &dquo;children with disabilities&dquo; in general (i.e., Helmstetter, Peck, & Giangreco, 1994;Schnorr, 1990).…”
Section: Methods Criteria For Including a Studymentioning
confidence: 99%
“…In summary then, these reviews and others have ex-amined younger children in preschool programs (Gresham, 1982;Guralnick, 1999), children with a variety of disabilities (Gresham, 1982;Hallenbeck & Kauffman, 1995), and only those in a particular educational setting (Hunt & Goetz, 1997). These diverse examinations and the numerous methodological issues in the studies as identified by the reviewers (Gottlieb, 1981;Gresham & MacMillan, 1997) We note Leinhardt and Pallay's (1982) (Buysse & Bailey, 1993;Slavin, 1984).…”
Section: The Most Appropriate Environment For the Edu-mentioning
confidence: 99%
“…In addition many teachers may not know how to handle learners with mental-health problems. A major concern that is often raised when a student with high support needs is included in a mainstream classroom is the fear that his or her presence and participation might detract and retard the academic progress of the non-disabled peers (Hunt & Goetz, 1997). Moreover, regular teachers often think that the placement of disabled learners in ordinary classrooms might influence teaching effectiveness (Myles & Simpson, 1989).…”
Section: Attitudes To Severely Disabled Learnersmentioning
confidence: 99%
“…These negative attitudes are gradually becoming positive with the wide availability of sensitization programs as well as preserve and in-service courses in special education. Hunt and Goetz (1997) reviewed 19 studies of inclusive educational programs, practices, and outcomes for students with severe disabilities. Their meta-analysis revealed that learners with severe disabilities were includable in ordinary schools, and that they could achieve positive academic and learning outcomes, contrary to the unfounded fears or concerns held by many stakeholders.…”
Section: Attitudes To Severely Disabled Learnersmentioning
confidence: 99%
“…The result then is that, when homework is counted as a means of assessing progress, the grades of students with disabilities are likely to suffer . In order to support students with disabilities who are in inclusive general education settings, additional support, or alternative techniques need to be utilized to maximize their homework success, which in turn will contribute to their full participation in general education classes Hunt & Goetz, 1997). Such assistance could include students learning to provide some of their own support techniques (Janney & Snell, 2000).…”
Section: Introductionmentioning
confidence: 99%